PENYUSUNAN JADWAL BELAJAR SEKOLAH MENENGAH YANG EFEKTIF MEMANFAATKAN KOMPUTERISASI SIMULASI - Agus Pribadi; Muhammad Yunus (SENTIA 2016, 2016)
Planning and managing implementation of the learning activities are required best arrangements through the making of learning schedule. Complexity and constraints in the making of learning schedule are able to influence effectiveness of the learning activities implementation. The making of learning schedule generally requires 1 month. Basic problems of the learning schedule making in senior high school are complexity, duplication and time consuming. Computerization is a solution to making of learning schedule well, simple process and precision.Teacher in charge for the learning schedule making is trained to computerize the learning schedule making. According to training result, teacher in charge could be able to computerize the learning schedule making. Limitations and shortcomings on the making of learning schedule can be solved by computerizing the making of learning schedule. 10 learning schedule items could be produced in once processing of the learning schedule making. The computerized of the learning schedule making is an opportunity to get school management effectively and efficiency. The learning activity will run at school well, effectively and efficiency.